2022
DOI: 10.48077/scihor.25(8).2022.37-48
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Сulture, Reproduction, and Productivity of Aromatic Plants of the Lamiaceae Family in the Central Polissia of Ukraine

Abstract: The introduction of new types of aromatic plants of the Lamiaceae family into the culture is relevant for the enrichment of the biological diversity of the flora of the Central Polissia of Ukraine, as well as for the expansion of the raw material base of spicy-aromatic, medicinal, food, decorative, and honey-bearing plants. The purpose of this study is to find methods of propagation of aromatic plants, best sowing times and feeding areas, and to obtain phytoraw and seed materials. Research methods: laboratory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, Ukrainian researchers Panfilova & Fedorchuk (2022) investigated the efficiency of biological preparations and mineral fertilisers application on the crops of Salvia officinalis L. under the conditions of the Southern Steppe zone of Ukraine, while their colleagues Svydenko et al (2022) performed robust investigations on the best genotypes for sage cultivation in the above-mentioned agro-climatic zone. Kotyuk et al (2022) conducted one of the most prospective and valuable studies on the cultivation of Salvia sclarea L. to establish the possibilities of the introduction and productivity of clary sage in the conditions of the Central Polissia zone. As a result, researchers found that the crop is prospective and deserves the attention of Ukrainian farmers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ukrainian researchers Panfilova & Fedorchuk (2022) investigated the efficiency of biological preparations and mineral fertilisers application on the crops of Salvia officinalis L. under the conditions of the Southern Steppe zone of Ukraine, while their colleagues Svydenko et al (2022) performed robust investigations on the best genotypes for sage cultivation in the above-mentioned agro-climatic zone. Kotyuk et al (2022) conducted one of the most prospective and valuable studies on the cultivation of Salvia sclarea L. to establish the possibilities of the introduction and productivity of clary sage in the conditions of the Central Polissia zone. As a result, researchers found that the crop is prospective and deserves the attention of Ukrainian farmers.…”
Section: Introductionmentioning
confidence: 99%